Relevansi asnaf zakat di era digital dalam kajian kontekstual terhadap transformasi distribusi zakat modern - Alifiyah, Nafilah; Wardana, Guntur Kusuma (Maliki Interdisciplinary Journal, 2026)
Zakat is an Islamic economic instrument that plays a role in creating social welfare and economic equality in society. The development of digital technology has brought changes to the zakat collection and distribution system through various digital platforms, making it more effective and efficient. However, this development also poses challenges regarding the relevance of the concept of zakat asnaf in the context of modern society. Therefore, a contextual study is needed regarding the relevance of zakat asnaf in the transformation of modern zakat distribution in the digital era. This study aims to analyze the relevance of the concept of zakat asnaf in the digital era and to understand the transformation of modern zakat distribution from an Islamic economic perspective. The study used a qualitative approach using library research. Data were obtained from scientific journals, books, regulations, and documents of zakat management institutions, then analyzed using descriptive-qualitative methods. The results show that the concept of zakat asnaf remains relevant, but requires a contextual approach to align with modern social developments. Digital transformation in zakat management can increase the effectiveness, transparency, and reach of zakat distribution, thus expected to support sustainable zakat welfare.